Implementasi Pelaksanaan Program Sosialisasi, dan Motivasi dalam Peningkatan Kesadaran Kebersihan Lingkungan Masyarakat (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2017)
With thepopulation growthis increasingand the progress ofhuman technologyis growing, garbageis a serious problemandneedhandlingcarefully, as directedbyinnovation-innovation thatisadequatein terms ofall aspects, be it social,economic aspects, as well astechnical aspects. Such conditionscan be predicted thatthe futureof hiscitywill producemoregarbage. Therefore,if nobettertreatmentfrom now onit willresult in achange ofbalancethat can harmthe environmentandis not expected tocontaminate the environmenteitherto water, soil, air, aestheticview ofa city, andcan bedetrimental to health.Forthat we need thecommunications madecleanlinessandlandscapingserviceswithmasyarakaattoprovide counselingabout the need tobe aware of thecleanliness ofthe environment, especiallyin an environmentthat stillthere isnomajorityofpeople who are lessaware oftheenvironmental hygienebecausetheyoccurat randomgarbage disposal. Keywords: Implementation Program, socialization, motivation, andawareness ofHygiene.